Diskusi Kamisan Rumah Baca Akkitanawa: Membincang Isu-Isu Kontemporer Komunikasi - Fadhillah S, Nurul; Nurjayanti, Nurjayanti; Samsuddin, Yati Bt (Jurusan Teknik Informatika dan Komputer, 2025)
The rapid development of digital technology has brought about significant changes in people's communication patterns, especially through social media. Unfortunately, this progress is not always accompanied by an adequate understanding of contemporary communication issues in the digital space. This community service activity aims to provide a broader understanding of contemporary communication issues to the general public, especially related to disability, gender, regulation, and fandom. Activities are carried out on an online platform by Google Meeting and organized by Rumah Baca Akkitanawa, Palopo, with participants from various backgrounds and domiciles, including from Eastern Indonesia such as Papua. The material was delivered through an interactive presentation followed by a reflective discussion session to explore the views and experiences of the participants. The results of the activity showed that many people still need further understanding regarding contemporary communication issues, especially in the realm of social media. As a solution, participants are equipped with critical thinking skills on these issues. Further service can be carried out in the form of practical training in the wise use of communication technology and the creation of educational modules for local communities, in order to strengthen sustainable digital awareness.